PENGARUH BIAYA PROMOSI DAN BIAYA DISTRIBUSI TERHADAP LABA USAHA PT. INDOFOOD SUKSES MAKMUR TBK - MONTARIS SILAEN; KARINA SILAEN (JURNAL ILMIAH SIMANTEK, 2021)
This study aims to find out (1) Whether there is an influence between promotional costs on operating profit, (2) Whetherthere is an influence between distribution costs on operating profit, (3) Whether there is an influence between promotionalcosts and distribution costs on operating profit at PT. Indofood Sukses Makmur Tbk in 2014 - 2020. Bound variables areoperating profit and free variables are promotional fees and distribution costs. This research uses the data collection methodrequired purposive sampling method then data analysis technique using linear regression of quantitative data in the form ofcorporate financial statements that have been audited by public accountants have been presented on the internet from theperiod of fiscal year 2014 to fiscal year 2020. Then in the analysis with multiple linear regressions. The results showed (1)there was a partial significant influence between promotional costs to PT's operating profit. Indofood Sukses Makmur Tbk,(2) has no partial impact between distribution costs to PT's operating profit. Indofood Sukses Makmur Tbk, (3) there is asignificant simultaneous influence of promotional costs and distribution costs on PT's operating profit. Indofood SuksesMakmur Tbk.